Didaktik Andragogi Islami Di BPSDM Aceh (Lembaga Studi Agama dan Masyarakat Aceh (LSAMA), 2022)
There is not enough room for discussion on adult education, especially in Basic Education and Training, Pim III, Pim IV, which are attended by ASN, with a duration of 3 months to 6 months. The educational process internalizes concepts and practices in order to familiarize the embedded knowledge, attitudes and skills for ASN. But in reality, Education and Training is something that is feared and worried by ASN who are participants in the training. In fact, there is an assumption that adult learning has been completed, when he is declared to have passed the CPNS (with a bachelor's degree). Whereas learning for a human child lasts a lifetime, by learning an ASN can also understand that work is worship to his God.